2002
DOI: 10.1089/089771502753754046
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Brain Temperature in Patients after Severe Head Injury: Relationship to Intracranial Pressure, Cerebral Perfusion Pressure, Cerebral Blood Flow, and Outcome

Abstract: Brain temperature was continuously measured in 58 patients after severe head injury and compared to rectal temperature, intracranial pressure, cerebral blood flow, and outcome after 3 months. The temperature difference between brain and rectal temperature was also calculated. Mild hypothermia (34-36 degrees C) was also used to treat uncontrollable intracranial pressure (ICP) above 20 mm Hg when other methods failed. Brain and rectal temperature were strongly correlated (r = 0.866; p < 0.001). Four groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 58 publications
9
90
1
4
Order By: Relevance
“…A review of this mixed evidence suggests that following acute neurological disease and injury, the human brain is at a higher temperature than body tissues [20]. However, variations in the patients' thermal state appear to have an impact on the brain-body temperature gradient; the greatest difference occurring during hypothermia with average brain temperature over 1°C lower than core body temperature [21]. These findings are consistent with models of heat transfer from brain to body core during hypothermia [22].…”
supporting
confidence: 52%
“…A review of this mixed evidence suggests that following acute neurological disease and injury, the human brain is at a higher temperature than body tissues [20]. However, variations in the patients' thermal state appear to have an impact on the brain-body temperature gradient; the greatest difference occurring during hypothermia with average brain temperature over 1°C lower than core body temperature [21]. These findings are consistent with models of heat transfer from brain to body core during hypothermia [22].…”
supporting
confidence: 52%
“…Alternatively, this inversion of the brain and bladder temperatures may have resulted from ischemia induced by low CBF, decreased cerebral metabolic demand, or changes in hypothalamic regulation due to pharmacological treatment (sedation, paracetamol) during hypothermia. 17) This study found that the difference between brain and bladder temperatures in the SDH group was significantly lower than that in the DAI group, possibly because the brain temperature in the DAI group was increased by the higher cerebral metabolism and CBF induced by DAI. In addition, the brain temperature in the SDH group may have been influenced by environmental factors.…”
Section: E Suehiro Et Almentioning
confidence: 59%
“…Some studies have looked at the differences between brain temperature and core temperature in a clinical setting, since the introduction of technology for direct measurement of brain temperature. 5,12,17,20) Brain temperature was much higher than rectal temperature if CPP was reduced to between 50 and 20 mmHg, indicating impaired CBF. 13) Furthermore, this difference decreased significantly as CPP was reduced to below 20 mmHg, indicating irreversible impairment of CBF.…”
Section: E Suehiro Et Almentioning
confidence: 99%
See 2 more Smart Citations